The Use of Mobile Apps in Learning English Language - Maryam Ameri (BIRCU, 2020)
Throughout and out of college, the use of technology has become an integral part of the learning process. Technology helps teachers to adapt lessons in the classroom, thereby improving the learning process, English as a second language/international. This paper discusses different attitudes which help English language learners by using technologies to increase their learning skills. Researcher indicates that the effective use of new technologies improves learners’ language learning skills.